Evaluation of Cardiovascular Involvement in Pediatric Behcet's Disease: Case Report and Literature Review with Intracardiac Thrombus - Serkan Türkuçar; Hatice Adıgüzel Dündar; Ceyhun Açarı; Erbil Ünsal (Erciyes Medical Journal, 2019)
Behcet's Disease (BD) is an inflammatory vasculitis with multisystem involvement. Typical manifestations such as oral-genital ulcerations, joint, skin, and ocular involvement usually occur during the initial period of the disease, whereas cardiac and vascular involvement may be seen in the later stages and in a more severe form of the disease. A 17-year-old male with a history of intracranial thrombosis due to BD was admitted with dyspnea and cough. A CT angiography revealed bilateral consolidation areas that were possibly compatible with pulmonary embolism. Further investigations conducted to find the origin of the embolism revealed one thrombus of 3x2 cm dimensions in the right ventricular apex (by echocardiography) and another one in the superficial branches of the right saphenous vein in the lower extremity. He responded well to early-onset immunosuppressive and steroid therapy. This case-based literature review was presented to emphasize the need for careful and detailed evaluation of thrombosis and vascular involvement in Behcet's Disease.